1989
DOI: 10.1007/bf02471618
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell emboli in the pectoral lymphatics of patients with breast cancer

Abstract: In order to investigate the possibility of local recurrence in the pectoral muscles of patients who undergo modified radical mastectomies, the cancer cell involvement of the lymphatics associated with the pectoralis major muscle was studied in 39 patients who underwent a standard radical mastectomy for Stage I-III breast cancer. Cancer cell emboli were found in the transpectoral lymphatics of 2 patients (2/39 = 5.1 per cent) and in the pectoral fascial lymphatics of 6 patients (6/39 = 15.4 per cent). Two patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…13 However, several studies have shown that PF invasion can occur when tumors are located within 5 mm of the PF and are unlikely to occur with more than 5-mm distance. 4,14 This suggests that a tumor-fascia distance of more than 5 mm could be interpreted as safe. Another important reason why the PF was never preserved according to the breast surgeons was because they are not familiar with this technique.…”
Section: Discussionmentioning
confidence: 98%
“…13 However, several studies have shown that PF invasion can occur when tumors are located within 5 mm of the PF and are unlikely to occur with more than 5-mm distance. 4,14 This suggests that a tumor-fascia distance of more than 5 mm could be interpreted as safe. Another important reason why the PF was never preserved according to the breast surgeons was because they are not familiar with this technique.…”
Section: Discussionmentioning
confidence: 98%